Promoterless, Nuclease‐Free Genome Editing Confers a Growth Advantage for Corrected Hepatocytes in Mice With Methylmalonic Acidemia. Issue 6 (21st May 2021) - Chandler, Randy J.; Venturoni, Leah E.; Liao, Jing; Hubbard, Brandon T.; Schneller, Jessica L.; Hoffmann, Victoria; Gordo, Susana; Zang, Shengwen; Ko, Chih‐Wei; Chau, Nelson; Chiang, Kyle; Kay, Mark A.; et al.
Abstract : Background and Aims: Adeno‐associated viral (AAV) gene therapy has shown great promise as an alternative treatment for metabolic disorders managed using liver transplantation, but remains limited by transgene loss and genotoxicity. Our study aims to test an AAV vector with a promoterless integrating cassette, designed to provide sustained hepatic transgene expression and reduced toxicity in comparison to canonical AAV therapy. Approach and Results: Our AAV vector was designed to insert a methylmalonyl‐CoA mutase ( MMUT ) transgene into the 3′ end of the albumin locus and tested in mouse models of methylmalonic acidemia (MMA). After neonatal delivery, we longitudinally evaluated hepatic transgene expression, plasma levels of methylmalonate, and the MMA biomarker, fibroblast growth factor 21 (Fgf21), as well as integration of MMUT in the albumin locus. At necropsy, we surveyed for AAV‐related hepatocellular carcinoma (HCC) in all treated MMA mice and control littermates. AAV‐mediated genome editing of MMUT into the albumin locus resulted in permanent hepatic correction in MMA mouse models, which was accompanied by decreased levels of methylmalonate and Fgf21, and improved survival without HCC. With time, levels of transgene expression increased and methylmalonate progressively decreased, whereas the number of albumin‐MMUT integrations and corrected hepatocytes in MMA mice increased, but not in similarly treated wild‐type animals. Additionally, expression of MMUT in the setting of MMA conferred a selective growth advantage upon edited cells, which potentiates the therapeutic response. Conclusions: In conclusion, our findings demonstrate that AAV‐mediated, promoterless, nuclease‐free genome editing at the albumin locus provides safe and durable therapeutic benefit in neonatally treated MMA mice.